Identifikasi, Kelimpahan dan Tipe Karakteristik Habitat Ikan Tembakul Desa Pasir Kabupaten Mempawah Kalimantan Barat - Dedi Irawan; Warsidah Warsidah; Syarif Irwan Nurdiansyah; Ikha Safitri; Arie Antasari Kushadiwijayanto (Barakuda'45, 2020)
Tembakul or mudskipper has the ability to adapt the condition of tidal area trough walking on the mud. The purpose of this research, wich held on February – March 2019 at Pasir Village Mempawah Regency, are to found out the species of tembakul on that area, with its abundance and the characteristic of its habitat. Sample taken from 3 sampling sites wich determinated by purposive method with the help of net for caught tool. The result of this research found 3 species of mudskipper, i.e Boleophthalmus boddarti, Periophthalmus schlosseri and P. chrysospilos. P. Schlosseri had the highest abundance (0,82 Ind/m²), followed by B. Boddarti 0,74 Ind/m² and P. Chrysospilos (0,52 Ind/m²). Site I had the highest abundance of mudskippers (0,94 Ind/m²), while site II was the lowest (0,53 Ind/m²). Based on the regression analysis of enviromental actors of its habitat, salinity had the big impact for mudskipper.